2020
DOI: 10.1108/ecam-09-2019-0475
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for BIM implementation: a Malaysian case study

Abstract: PurposeThis paper aimed to identify critical success factors (CSFs) of building information modeling (BIM) implementation among architectural, engineering and construction (AEC) firms in Malaysia using quantitative statistical methods.Design/methodology/approachA questionnaire survey was conducted on the population of all AEC firms in Malaysia to rank the relative importance of 15 success factors (SFs) for BIM implementation in the firm on a 5-point Likert scale. The sampling frame consisted of all members reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 118 publications
(165 reference statements)
2
47
1
Order By: Relevance
“…More precise characteristics of BIM commitment have been uncovered by Olugboyega and Windapo (2019), which define BIM commitment as the whole dedication of construction organisations' top management to BIM adaption, adoption, application and execution. Investigations such as Munir et al (2020) and Sinoh et al (2020) have highlighted top management commitment as a significant driving force for BIM adoption, lending support to the argument for BIM commitment as an essential component of a BIM implementation strategy. Based on this context, this study develops a hypothesis stating that BIM commitment is important for increasing the proportion of BIM adoption (Hypothesis 3).…”
Section: Conceptualising the Four-wheel Model Of Bim Implementationmentioning
confidence: 94%
“…More precise characteristics of BIM commitment have been uncovered by Olugboyega and Windapo (2019), which define BIM commitment as the whole dedication of construction organisations' top management to BIM adaption, adoption, application and execution. Investigations such as Munir et al (2020) and Sinoh et al (2020) have highlighted top management commitment as a significant driving force for BIM adoption, lending support to the argument for BIM commitment as an essential component of a BIM implementation strategy. Based on this context, this study develops a hypothesis stating that BIM commitment is important for increasing the proportion of BIM adoption (Hypothesis 3).…”
Section: Conceptualising the Four-wheel Model Of Bim Implementationmentioning
confidence: 94%
“…Unlike previous research, this study revealed the original root factor of LBE. Although the importance of BIM education has been highlighted in previous studies (Sinoh et al, 2020;Elmalı and Bayram, 2022), there is no existing research that evaluates and incorporates the lack of BIM education as a latent factor at former researches. Some previous studies (Chan et al, 2019a(Chan et al, , 2019bLiao et al, 2019) have addressed this issue within the context of training.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of BIM is rapidly increasing worldwide, it is still in its beginning phase in Turkey (Aladag et al, 2016;Simsek and Uzun, 2021) like in other developing countries. According to Antwi-Afari et al (2018), developing countries, such as India (Nanajkar, 2014;Ahuja et al, 2016), Singapore (Liao and Teo, 2017), Nigeria (Amuda-Yusuf, 2018; Olanrewaju et al, 2020;Olugboyega and Windapo, 2021), Iraq (Hatem et al, 2018), China (Zhang et al, 2020;Tu et al, 2021;Zhao and Wu, 2017;Zhou et al, 2019), Iran (Hosseini et al, 2016), Jordan (Btoush and Haron, 2017), and Malaysia (Rogers et al, 2015;Yaakob et al, 2016;Sinoh et al, 2020), the implementation of BIM is lagging. However, significant attempts have been made to investigate the limiting causes of BIM implementation and how BIM can be adapted to the construction industries in developing countries (Shahruddin et al, 2022;Sinoh et al, 2020).…”
Section: Root Factors Limiting Bim Implementationmentioning
confidence: 99%
See 2 more Smart Citations